SIRT1 modulates cell cycle progression by regulating CHK2 acetylation−phosphorylation - Zhang, Wenyu (Cell Death Differ, 2019)
Both the stress-response protein, SIRT1, and the cell cycle checkpoint kinase, CHK2, play critical roles in aging and cancer via the modulation of cellular homeostasis and the maintenance of genomic integrity. However, the underlying mechanism linking the two pathways remains elusive. Here, we show that SIRT1 functions as a modifier of CHK2 in cell cycle control. Specifically, SIRT1 interacts with CHK2 and deacetylates it at lysine 520 residue, which suppresses CHK2 phosphorylation, dimerization, and thus activation. SIRT1 depletion induces CHK2 hyperactivation-mediated cell cycle arrest and subsequent cell death. In vivo, genetic deletion of Chk2 rescues the neonatal lethality of Sirt1(−/−) mice, consistent with the role of SIRT1 in preventing CHK2 hyperactivation. Together, these results suggest that CHK2 mediates the function of SIRT1 in cell cycle progression, and may provide new insights into modulating cellular homeostasis and maintaining genomic integrity in the prevention of aging and cancer.